Mechanically induced thermal breakdown in magnetic shuttle structures. (20th June 2018) - Ilinskaya, O A; Kulinich, S I; Krive, I V; Shekhter, R I; Park, H C; Jonson, M
Abstract: A theory of a thermally induced single-electron 'shuttling' instability in a magnetic nano-mechanical device subject to an external magnetic field is presented in the Coulomb blockade regime of electron transport. The model magnetic shuttle device considered comprises a movable metallic grain suspended between two magnetic leads, which are kept at different temperatures and assumed to be fully spin-polarized with anti-parallel magnetizations. For a given temperature difference shuttling is found to occur for a region of external magnetic fields between a lower and an upper critical field strength, which separate the shuttling regime from normal small-amplitude 'vibronic' regimes. We find that (i) the upper critical magnetic field saturates to a constant value in the high temperature limit and that the shuttle instability domain expands with a decrease of the temperature; (ii) the lower critical magnetic field depends not only on the temperature-independent phenomenological friction coefficient used in the model but also on intrinsic friction (which vanishes in the high temperature limit) caused by magnetic exchange forces and electron tunneling between the quantum dot and the leads. The feasibility of using thermally driven magnetic shuttle systems to harvest thermal breakdown phenomena is discussed.